(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Objective: Septic abortion is a life threatening complication of induced abortion. Being a tertiary referral hospital in Bangladesh, Sir Salimullah Medical College and Mitford Hospital often deals with such cases of septic abortion. This research work was conducted with the aim of evaluation of frequency, complications and outcome of septic abortion in this institute. Method: A cross sectional observational study was conducted from January 2016 to December 2016 in the department of Obstetrics and Gynaecology, Sir Salimullah Medical College and Mitford Hospital, Bangladesh. All cases of septic abortion admitted in the department were included in the study. Results: During one-year period total number of Gynaecological admission cases were 11,351, of which 1065 were abortion cases, among them 28 cases were diagnosed as septic abortion. The frequency of septic abortion thus was 2.6% of the abortion admitted cases. Age range of the patients was between 15 to 45years. Majority (60.71%) of the cases were grand multigravida, belonging to poor socioeconomic group (71%). Most of the patients (68%) came with haemorrhage. The most frequent method (50%) used for termination of pregnancy in this study was Menstrual Regulation (MR) in unhygienic environment. Mostly (57.14%) the patients were managed by evacuation and curettage. Laparotomy was also needed for the definitive management of two patients. Maternal mortality in this study group was one out of 28(3.7%). Conclusion: Septic abortion contributes significantly to maternal morbidity and mortality. Proper use of contraceptives, avoidance of induced abortion in unhygienic condition can reduce the moribund consequences. In this study one maternal death among 28 septic abortion cases indicate proper standard of care of the hospital. Bangladesh J Obstet Gynaecol, 2020; Vol. 35(1): 3-6